The principle of Wasatiyyah as a higher objective in Islam: a historical survey - Muhammad, Muneer Kuttiyani; Abdul Rahim, Adibah (IIUM Press, International Islamic University Malaysia, 2017)
Both early and modern scholars have deliberated extensively on the principle of wasatiyyah with its various interpretations. Despite of a wide deliberation on the principle of wastiyyah, it had not been perceived through the shariah point of view, and there was no study which directly relates it with the objectives of shariah. This paper, therefore, examines the necessity of wasatiyyah from the perspective of shariah. It attempts at highlighting the principle of wasatiyyah as one of the objectives of shariah. In doing so, the Quranic and prophetic texts dealing with the principle of wasatiyyah along with the views of early and modern scholars are examined. In addition, this paper also examines some approaches of wastiyyah by Muslim reformists. They demonstrated the different manifestations of wasatiyyah and its significance in accordance with the needs and circumstances of the society. Based on the significance of wasatiyyah, this paper concludes that it can be considered as one of the fundamental principles of shariah. In other words, the principle of wasatiyyah should be acknowledged as a higher objective of the shariah which must be obtained at both individual as well as collective level.